EFFECTIVENESS OF TEACHING BASED ON SELF-REGULATED LEARNING THEORY IN COGNITIVE ACHIEVEMENT AND LEARNING THE BASKETBALL SHOOTING SKILL AMONG FEMALE STUDENTS - -hussein hassan, Wasan abdul (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2025)
The research, titled "Effectiveness of Teaching Based on Self-Regulated Learning Theory in Cognitive Achievement and Learning the Basketball Shooting Skill Among Female Students," highlights the importance of employing innovative educational strategies to improve learning outcomes. This theory empowers learners to take control of their learning process by setting clear goals, utilizing suitable strategies to achieve them, and continuously assessing their performance for improvement. The study focuses on developing the basketball shooting skill, an essential skill that requires concentration and precision, along with enhancing cognitive achievement related to its technical principles. The research involved third-year female students from the College of Education for Women at the University of Kufa, divided into two groups: an experimental group taught using the self-regulated learning strategy and a control group relying on traditional methods. The experimental method was employed to evaluate the impact of the educational program, which spanned 16 teaching units over 8 weeks. The program was designed to include incremental exercises and tasks fostering learners' independence and ability to apply theoretical concepts in practice. The results showed that the experimental group significantly outperformed the control group in cognitive achievement and shooting accuracy, underscoring the effectiveness of teaching based on self-regulated learning. The study concluded that this strategy enhances students' autonomy, improves their cognitive and skill performance, and provides a dynamic and engaging learning environment. The researcher recommended adopting such educational strategies in curricula, emphasizing the importance of using supportive teaching tools and integrating composite exercises with skill learning. This approach contributes to enhancing students' cognitive and motor performance in sports and other fields. Future studies were suggested to explore broader applications of self-regulated learning theory in various educational domains.